Vascular ultrasound for monitoring of inflammatory activity in Takayasu arteritis. (10th November 2019) - Svensson, Christina; Eriksson, Per; Zachrisson, Helene
Summary: Background: Takayasu arteritis (TA) is a rare large‐vessel arteritis that primarily affects the aorta and its major branches. The aim of this study was to describe the value of high frequency ultrasound for monitoring of inflammatory activity. Methods: Twenty‐five patients, range 11–71 years, diagnosed with TA were investigated with duplex ultrasound (DUS) including follow‐up studies. Twenty‐five healthy controls were also investigated. Nine patients had newly diagnosed active TA. Sixteen patients had stable/inactive disease at baseline DUS, and TA was diagnosed median 4·5 years previously. Intima–media thickness (IMT), vessel and lumen diameter were measured in the carotid arteries, central neck arteries and the aortic arch. The vessel walls were studied qualitatively. The Takayasu ultrasound index was created for inflammatory activity scoring. Results: Intima–media thickness in common carotid artery (CCA) was (median and 25–75 percentile parenthetic) 2·3 mm (1·7–2·9) in clinically active TA, 1·2 mm (1·1–1·6) in clinically stable TA ( P <0·001) and 0·5 mm (0·5–0·6) in healthy controls ( P <0·001). Clinically active TA had prominent increase in IMT and/or increased vessel diameter, and/or intramural arteries, and/or hypoechogenic areas interpreted as oedema in the vessel wall. TA in clinical remission was characterized by increased IMT with medium to high echogenicity with or without fibrotic stripes. The Takayasu ultrasound index was higher in patients with active disease versus treated disease, 2·55 (1·60–3·05) versus 1·30 (1·00–1·58), ( P = 0·003). Conclusion: DUS is an excellent tool to monitor inflammatory changes in the vessel wall in TA. Further DUS studies in larger patient populations are warranted.